Conceptual study on extraction of formic acid from the electrolyte after electroreduction of CO2: Desalination and dehydration using a high-silica chabazite zeolite membrane - Norihiro Suzuki; Rumi Katsukawa; Naoya Ishida; Yuta Shiroma; Tsugumi Kagaya; Takeshi Kondo; Makoto Yuasa; Chiaki Terashima; Akira Fujishima (Heliyon, 2023)
Here, we propose a two-step pervaporation system with a high-silica CHA (chabazite) membrane, which has sufficient resistance to water and acid, to demonstrate the extraction and condensation of the formic acid formed by electroreduction of CO2. The kinetic diameters of water and formic acid are similar and smaller than the pore size of CHA, while the hydrated electrolyte ions (e.g., K+ and Cl−) are larger than the pore size of CHA. Consequently, the electrolyte ions are separated from the mixture of water and formic acid in the first desalination process, and then water molecules are easily removed from the mixture in the second dehydration process. From 300 ml of an approximately 3 wt% formic acid aqueous solution containing 0.5 M KCl, 10 ml of 18.2 wt% formic acid was obtained.